2022
DOI: 10.3389/fpubh.2022.966989
|View full text |Cite
|
Sign up to set email alerts
|

Changes in leisure activities of the elderly due to the COVID-19 in Korea

Abstract: Recreational activities such as physical and social activities are key components of a healthy life for the elderly. Since the outbreak of Corona 19, leisure facilities such as indoor sports facilities, religious facilities, and cultural facilities have been closed, and group activities such as volunteer activities and clubs are also being held under control. These measures are expected to bring about many changes in the leisure activities of the elderly. In this study, an empirical analysis was made on how CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Generally, older people limited their daily routine activities and reduced PA level, for example they had to perform PA in their own room or in corridors. Some studies reported that older people who had to stay at home for a long time during the COVID-19 experienced serious fear of movement, an elevated risk of falling, and low PA level [26,27]. We found that Tai Chi participators reported a higher proportion of PA than other peers.…”
Section: Discussionmentioning
confidence: 58%
“…Generally, older people limited their daily routine activities and reduced PA level, for example they had to perform PA in their own room or in corridors. Some studies reported that older people who had to stay at home for a long time during the COVID-19 experienced serious fear of movement, an elevated risk of falling, and low PA level [26,27]. We found that Tai Chi participators reported a higher proportion of PA than other peers.…”
Section: Discussionmentioning
confidence: 58%
“…Our results have also shown that there was no potential association between the quality of pedestrian facilities or commercial facilities and PAB of older adults ( Kim, Park & Kang, 2022 ). Consequently, it could be concluded that there was an interaction between environmental factors and individual behaviors.…”
Section: Disscussionsmentioning
confidence: 49%
“…On the one hand, the findings of this study revealed that participating in leisure activities was associated with an average survival time that was approximately 20 months longer than that of non-participants. This difference could be because engaging in leisure activities is linked to a favorable lifestyle, improved mental health, and a reduced risk of chronic diseases ( 6 , 21 ). On the other hand, significant differences in survival status were observed among older adults involved in different types of leisure activities.…”
Section: Discussionmentioning
confidence: 99%